Multidirectional memory : remembering the Holocaust in the age of decolonization - Rothberg, Michael (Cultural memory in the present, 2009)
Introduction : theorizing multidirectional memory in a transnational age -- Boomerang effects : bare life, trauma, and the colonial turn in Holocaust studies -- At the limits of Eurocentrism : Hannah Arendt's The origins of totalitarianism -- "Un choc en retour": Aimé Césaire's discourses on colonialism and genocide -- Migrations of memory : ruins, ghettos, diasporas -- W.E.B. Du Bois in Warsaw : Holocaust memory and the color line -- Anachronistic aesthetics : André Schwarz-Bart and Caryl Phillips on the ruins of memory -- Truth, torture, testimony : Holocaust memory during the Algerian War -- The work of testimony in the age of decolonization : chronicle of a summer and the emergence of the Holocaust survivor -- The counterpublic witness : Charlotte Delbo's Les belles lettres -- October 17, 1961 : a site of Holocaust memory? -- A tale of three ghettos : race, gender, and "universality" around 1961 -- Hidden children : the ethics of multigenerational memory after 1961 -- Epilogue : multidirectional memory in an age of occupations